Do inventory practices correlate with inventory management performance?: a cross-sectional study in Malaysian public hospitals / Fariza Ahmad Mahyadin@Mahidin ... [et al.] - Ahmad Mahyadin@Mahidin, Fariza; Yusoff, Rushami Zien; Saad, Rohaizah; Mohd Asaad, Norhasni (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
The study is aimed to evaluate the correlation between inventory management practices, represented by inventory control towards inventory management performance. A cross-sectional, descriptive study was undertaken. A total of 143 public hospitals in Malaysia were approached for the study using online questionnaires. Descriptive statistics were used for elaborating demographic characteristics while for inferential statistics, a Pearson Correlation Analysis was used to test the effects of inventory control on inventory management performance. Analysis were performed using SPSS 21.0. Out of 103 online questionnaires, 81 were returned with a response rate of 78.64%. Positive linear correlations between inventory control (r = 0.799, n=81, p < 0.01) towards inventory management performance were observed. Therefore, the results as portrayed showed that by increasing the inventory control, it will lead to increasing inventory management performance. Positive correlation between both variables will further help in the prevention and management of inventory (drugs). Therefore, a good practice of controlling drug management should be implemented by public hospitals in Malaysia. Also, learning on drugs management from Pharmacy Department of public hospitals could be transferable to pharmacy department of private hospitals and inventory department of other organisations. This study is limited to the Malaysian public healthcare sector. In order to improve generalisability, this study could be replicated in private hospitals and other industries sector. The findings shed light and provided useful guidelines to the Main Medical Store (MMS) of public hospitals to better improve the inventory control (drug management) towards inventory management performance. Suggestions for future research are also included.